Penerapan Framework Information Technology Infrastructure Library (ITIL) Versi 3 pada Domain Service Operation untuk menganalisa Manajemen Layanan Teknologi Informasi - Afrijal Farhan Deyantoro; Resad Setyadi; Yudha Saintika (STMIK Budi Darma, 2022)
Information Technology (IT) in the era of the Industrial revolution 4.0 is increasingly developing and changing the way humans complete all work. Advances in technology have caused automation/computerization in business management to be fast. Computerization helps humans improve performance and save resources in the process of working on it. The use of IT really supports the objectives of government administration so that it must pay attention to the efficiency of resource use and risk management. ATR/ BPN Purbalingga as one of the government agencies has used the use of services through the use of the ATR / BPN Purbalingga website. The role of important websites in the organization includes ATR/BPN Purbalingga. ATR / BPN shows several problems such as tools in the website are lacking and there are often server downs. The purpose of this study is the analysis of IT service management on websites kkp2.atrbpn.go.id using the ITIL Framework V.3 domain service operation. The research data analysis method uses quantitative methods by using SPSS measuring instruments. ITIL model V.3 as a medium of analysis of questionnaire data and to obtain the results of the analysis of the level of maturity of IT service management. The results of this study are recommendations for the maturity level of IT service management of the ATR / BPN website for the progress of improving website performance. The result of the maturity value on the website kkp2.atrbpn.go.id on the subdomain service operation domain service management as a practice by obtaining an average of 3.97. Service operation principles with an average of 3.27. Service operation processes earned an average of 2.95. Common service operation with an average of 4. Organizing service operations with an average of 4.12. Service operation technology consideration with an average of 3.8. Implementing service operations with an average of 3.3. The average total obtained from all domain service operations is 3.1 at level 3 (defined) which means it is important to carry out basic processes and document each process and standardize in order to reach the expected level